Probiotics, Symptoms, and Gut Microbiota: What Are the Relations? A Randomized Controlled Trial in Subjects with Irritable Bowel Syndrome. (31st July 2012) - Farup, Per G.; Jacobsen, Morten; Ligaarden, Solveig C.; Rudi, Knut
Abstract : Introduction . Knowledge of the mechanism of action of probiotics in subjects with irritable bowel syndrome (IBS) is imperfect. Objective . This trial aimed at discriminating between a direct effect on the gut wall and an indirect effect caused by modulation of the fecal microbiota. Design . Randomized, double-blind, crossover trial. Material and Methods . Patients with IBS were given one capsule of 10 10 CFU L. plantarum MF 1298 or placebo once daily. Symptoms were registered (score 0–15) and feces collected at the end of each period. The gut microbiota was analyzed with 16S rRNA gene analyses and results reported as proportions of Bacteroides, Faecalibacterium, and Lachnospiraceae and Simpson's D diversity score. Results . Sixteen participants (11 women) with a mean age of 50 years (SD 11) were available for the analyses. Intake of L. plantarum MF 1298 was associated with a significant aggravation of symptoms, but neither intake of L. plantarum MF 1298 nor symptoms were associated with the composition of the fecal microbiota ( P values >0.10). Conclusions . The trial indicates that the symptomatic aggravation related to intake of L. plantarum MF 1298 was a direct effect of the microbe on the gut wall and not caused by changes in the fecal microbiota.